Bigelow's drive and memory troubleshooting pocket reference - Bigelow, Stephen J. (McGraw-Hill, 2000)
The hugely popular, bestselling Pocket Reference series has been extended to cover one of the major problems faced by PC technicians--Drive and Memory. Designed as a technician-level reference, this pocket-sized guide covers all the essential information needed to diagnose and repair common computer storage systems.